Application of Band Ratio Technique To Distinguish The Surface Features for Sea Najaf Area Using Landsat (ETM+) Imagery - Ebtihal T. Hassan; Hussain M. Ali (Al-Qadisiyah Journal of Pure Science, 2017)
In this research applying ratios packets technique spectral (Band Ratio) todetermined the properties of the earth surface and discrimination of land cover types.Where the GPS device has been used to determine the study sites and match these siteswith satellite image. The study relied on a digital space image of satellite Landsat-7where, six spectral bands has been used for Enhancement Thematic Mapper plus(ETM+) sensor except the thermal sixth band, where spectral ratios applied of(ETM+)bands separately to detect different types of surface. Spectral reflectance of thedifferent samples surface has been measured using a Erdas imagine 8.4 program . Theresults showed that the surface samples which value of band ratios more than oneshowed high spectral reflectance in the image of the corresponding ratios bands whichappeared brightness color where it distinguished between the different units of thesurface . After that several images of the spectral ratios have been tested, three spectralratios images has been collected to create collection image for colored image showingthe surface landmarks clearly different . Finally, the results showed the effectiveness ofspectral band ratios technology to identify and distinguish the different features of theearth surface.